1999
DOI: 10.1108/09534819910282153
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory analysis of definitions and applications of spirituality in the workplace

Abstract: In response to the rising interest in``spirituality in the workplace'', an exploratory analysis of text passages expressing definitions and applications of the topic was conducted. A grounded theory process applying thematic and network analysis techniques was used to examine text samples from three different sources: e-mail, survey responses, and a literature search. Throughout the investigation an emphasis was placed on maintaining the multiplicity of definitions and applications of``spirituality in the work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(64 citation statements)
references
References 6 publications
0
58
0
6
Order By: Relevance
“…The reason makes organizations be interested in workplace spirituality is the increase on the organizational effectiveness. The experimental evidences show the positive relationship between workplace spirituality and creativity (Freshman, 1999), honesty and trust within organization, Increased sense of personal success, organizational commitment, job different behaviors such as job satisfaction, occupational participation, decreasing the desire to quit, and organization-based self-esteem. There are various definitions and perspectives about the personal nature of spirituality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reason makes organizations be interested in workplace spirituality is the increase on the organizational effectiveness. The experimental evidences show the positive relationship between workplace spirituality and creativity (Freshman, 1999), honesty and trust within organization, Increased sense of personal success, organizational commitment, job different behaviors such as job satisfaction, occupational participation, decreasing the desire to quit, and organization-based self-esteem. There are various definitions and perspectives about the personal nature of spirituality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the view of organizational sociology, Sheep (2006) studied spirituality and indicated that the influences of workplace spirituality are beyond individual, organizational, and social levels. With regard to individuals, Freshman (1999) suggested that spirituality could result in new consciousness, which becomes an institution that will reinforce creativity. Tischler (1999) indicated that self-realization is a major cause to explore spirituality.…”
Section: Organizational Spirituality and Workplace Spiritualitymentioning
confidence: 99%
“…Tischler (1999) indicated that self-realization is a major cause to explore spirituality. Freshman (1999) suggested including self-realization in spiritual activities to facilitate employees' self-realization attitudes and morales at work. Ketchand and Strawser (2001) indicated that commitment in workplace spirituality results in employees' sense of belonging.…”
Section: Organizational Spirituality and Workplace Spiritualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the use of such interviewing is common in the SWP field (see e.g. Freshman, 1999;Marques, 2004;Neal, 2000). Interviews with the managers occurred in Auckland, New Zealand at the end of 2012 either in their place of work or in public spaces.…”
Section: Samplementioning
confidence: 99%